Surgical management of tumor-positive interval node in melanoma patients: An observational study. Issue 18 (May 2018) - Nacchiero, Eleonora; Vestita, Michelangelo; Robusto, Fabio; Maruccia, Michele; Annoscia, Paolo; Giudice, Giuseppe
Abstract : Abstract: The presence of interval nodes (IN) in melanoma is testified in several studies and sometimes these lymph nodes can contain metastatic disease. Currently there are no guidelines about the management of patients with tumor-positive INs. We enrolled all patients affected by melanoma who underwent sentinel lymph node biopsy (SLNB) in a single institution. All patients with tumor-positive IN underwent the lymphadenectomy of the subsequent draining lymphatic field. Prognosis of IN+-patients was compared with subjects with positive SLNB in usual field through Kaplan-Meier and multivariate Cox regression analysis. Overall 596 subjects underwent lymphoscintigraphy and one or more INs were identified in 94 (15.8%) patients. The mean number of sentinel lymph nodes (SNs) identified per patient was significantly higher in patients with INs. Macrometastasis were more common in patients with INs. Matched pair analysis testified a statistically significant better prognosis in patients with positive-INs when compared with patients with positive SNs in usual side with the same demographic and clinical characteristics. These findings were confirmed both in analysis of 10-year recurrence-free period, then in 10-years overall survival analysis. Lymphadenectomy of the lymphatic draining field beyond positive-IN testify has proved to be a safe procedure that may improve prognosis in melanoma patients with tumor-positive INs. The better prognosis of patients with tumor-positive INs undergoing lymphadenectomy may be justified by the earlier treatment of lymphatic metastases. Further multicentric comparative studies are needed to evaluate possible impact of this procedure on prognosis of melanoma patients.